WTO and FTAA services trade negotiations : challenges for developing countries with special reference to CARICOM - Majluf, Luis Abugattas (Caribbean RNM/IDB Project Christ ChurchBB, 2001)
Analyses the status of the negotiations on services in the WTO and in the FTAA, with the objective of highlighting the main issues on the agenda in these fora, and identifying the issues that CARICOM countries should deal with in those processes.